A psychotherapist speaks - McCaul, Jennifer (PINS-Psychology in Society, 2026)
Book review I Jerman, N (1987) Why psychotherapy? London: Free Association Books, ISBN O 946960 72 0 pbk. Why psychotherapy? is a highly personal view of the role of psychotherapy and its process at both the individual and the social level. The personal nature of the text affects not only the content of the book but its structure and its mode of expression. While the documentation of Herman's therapeutic philosophy is interesting, the eulogistic style of expression is often intrusive and irritating. Although the book is divided into clear chapters, its structure is determined more by the conversational style of the text.